Determinants of complicance with mandatory disclosure: research evidence - Fernandes, S.; Lourenço, I. (Corporate Ownership And Control, 2018)
This study analyses research evidence on the determinants of compliance with mandatory disclosure requirements, classified in four main areas: business characteristics, country characteristics, enforcement and corporate governance. The literature concerning the compliance with mandatory disclosure requirements is a relatively recent field of research, when compared to the literature on voluntary disclosure. Given the well-known economic benefits of disclosure, it is of great interest to academics and practitioners to understand the incentives that explain the behaviour of firms in terms of compliance with disclosure requirements. This review provides several insights. First, although the business characteristics found in different studies as explanatory factors for the level of compliance are not always the same, there are four business characteristics that predominate as explanatory factors of the level of compliance with disclosure requirements: the firm’s size, the firm’s profitability, the type of auditor, and the level of internationalization. Second, the country characteristics and the enforcement have always proved to be relevant when analysing the level of compliance with mandatory disclosure requirements, independently of the approach used. Third, some corporate governance characteristics (including the nature of the board members and the type of ownership/control) begin to emerge as determinants of the level of compliance with mandatory disclosure. Overall, whereas research on the determinants of compliance with mandatory disclosure requirements provides relevant insights, it does not yet provide a sufficient accumulation of empirical evidence. Based on this, we develop suggestions for future research, highlighting the importance of analysing the role of corporate governance on the level of compliance with mandatory disclosure requirements